Cost saving, patient centered algorithm for progenitor cell mobilization for autologous hematopoietic cell transplantation. Issue 4 (12th March 2021) - Sanikommu, Srinivasa Reddy; Reese, Emily S.; He, Jiaxian; Lee, Carlos; Ai, Jing; Butler, Candace M.; Jacobs, Ryan; Hu, Bei; Atrash, Shebli; Trivedi, Jigar; Bhutani, Manisha; Voorhees, Peter; et al.
Abstract: Administration of plerixafor with granulocyte‐colony stimulating factor (G‐CSF) mobilizes CD34+ cells much more effectively than G‐CSF alone, but cost generally limits plerixafor use to patients at high risk of insufficient CD34+ cell collection based on low peripheral blood (PB) CD34+ counts following 4 days of G‐CSF. We analyzed costs associated with administering plerixafor to patients with higher day 4 CD34+ cell counts to decrease apheresis days and explored the use of a fixed split dose of plerixafor instead of weight‐based dosing. We analyzed 235 patients with plasma cell disorders or non‐Hodgkin's lymphoma who underwent progenitor cell mobilization and autologous hematopoietic cell transplantation (AHCT) between March 2014 and December 2017. Two hundred ten (89%) received G‐CSF plus Plerixafor and 25 (11%) received G‐CSF alone. Overall, 180 patients (77%) collected in 1 day, 53 (22%) in 2 days and 2 (1%) in 3 days. Based on our data, we present a probabilistic algorithm to identify patients likely to require more than one day of collection using G‐CSF alone. CD34+ cell yield, ANC and platelet recovery were not significantly different between fixed and standard dose plerixafor. Plerixafor enabled collection in 1 day and with estimated savings of 5000, compared to patients who did not receive plerixafor and required collection for three days. While collection and processing costs and patient populations vary among institutions, our results suggest re‐evaluation of current algorithms.